Simple And Rapid Detection Of Salmonella Strains By Direct PCR Amplification Of The HilA Gene - S.G. Pathmanathan; N. Cardona-Castro; M. M. Sa´nchez-Jime´nez; M. M. Correa-Ochoa; S. D. Puthucheary; K. L. Thong (Microbiology Society, 2024)
Indexed by SCOPUS